Analisis Daya Tampung Lahan Pemakaman di Kota Makassar - Khalil Agus, Muhammad Hilmy; Budiharto, Tri; Aksa, Kamran (Journal of Urban Planning Studies, 2023)
This study aims to determine the remaining cemeteries and the capacity of cemeteries in Makassar City for the next 20 years and to develop directions for the development of cemeteries in Makassar City. This study uses descriptive analysis methods, population projections, burial land capacity and swot analysis. Based on the results of the analysis of the capacity of public cemeteries in Makassar City, they are no longer able to accommodate the number of deaths until 2041 with a normal system and based on the results of the swot analysis for directions in the development of meeting the needs of cemeteries in Makassar City can be carried out in various ways, namely: optimizing cemeteries and Utilization of regulations related to stake prices for non-native residents of Makassar City to control limited land for cemeteries.